Os movimentos curriculares inventivos nos encontros com crianças do primeiro ano do Ensino Fundamental I - Vargas, Viviane de Moraes Garcia (2023)
This dissertation is an invitation to experiences in a Municipal Elementary School (EMEF, in Portuguese). It has the form of an unpredictable journey through the production of other types of curricula involving first grade children and teachers. Therefore, our objective is mapping creative curricular initiatives produced by children and teachers in daily encounters and activities of a first-grade group. The authors that assisted us in thinking about life, knowledge building, curriculum building, encounters, childhood, children, and creativity in relation to the Philosophy of Difference were Deleuze, Carvalho, Kastrup, Guattari, Delboni, Silva, amongst many others. Consequently, they became the voices that guided us towards problematizing the following question: Which encounters or activities produce creative curriculum-building actions in a first-grade group? The research was conducted in a public elementary school in the city of Serra, in the state of Espírito Santo. We used these actions as the methodological path with children and teachers that, immersed in the school activities with their journals and cameras in hand, wish to record the workflows and care that trespass the researchers. We conclude that the strength and power of these encounters and events, assisted by literature, drawings, and photographs of this first grade group are able to produce creative curricular initiatives. Upon the composition of this dissertation, the research product presents collective experimentations with photographical evidence and the narratives of children and teachers, problematizing the images of school, curriculum, and childhood through the eyes of the children, therefore producing new creative initiatives.